2012
DOI: 10.1371/journal.pone.0052276
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Influences the Deposition of Critical Complement C3 Levels Required for the Killing of Burkholderia pseudomallei via NADPH-Oxidase Induction by Human Neutrophils

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis and is a major mediator of sepsis in its endemic areas. Because of the low LD50 via aerosols and resistance to multiple antibiotics, it is considered a Tier 1 select agent by the CDC and APHIS. B. pseudomallei is an encapsulated bacterium that can infect, multiply, and persist within a variety of host cell types. In vivo studies suggest that macrophages and neutrophils are important for controlling B. pseudomallei infections, however few details a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 99 publications
5
43
0
Order By: Relevance
“…Previous studies have reported mixed results as to the ability of neutrophils to kill Bp. However, a more recent study indicated that human neutrophils could efficiently clear Bp, but only if they displayed at least a minimal threshold of complement deposition on its surface [62]. Our findings are most similar to this study, although the kinetics of murine ROS appears to be faster, of shorter duration, and of lower magnitude compared to that exhibited by human neutrophils, based on the in vitro findings.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Previous studies have reported mixed results as to the ability of neutrophils to kill Bp. However, a more recent study indicated that human neutrophils could efficiently clear Bp, but only if they displayed at least a minimal threshold of complement deposition on its surface [62]. Our findings are most similar to this study, although the kinetics of murine ROS appears to be faster, of shorter duration, and of lower magnitude compared to that exhibited by human neutrophils, based on the in vitro findings.…”
Section: Discussionsupporting
confidence: 87%
“…In certain bacteria it is suggested their LPS binds complement components associated with the membrane attack complex at a distance from the bacterial surface, thus not allowing insertion into the bacterial outer membrane [101], and such a mechanism could explain why both Bp and Bt are serum-resistant, as they produce similar type II O-antigenic polysaccharide [64], [86], [102]. It is possible that the most prominent effect mediated by capsule was the ability to reduce complement deposition on the outer surface, which has also been reported by others [62], [63]. The significance of this property is reflected in our finding that complement deposition is required for neutrophil-mediated killing of Bp, but only if a certain level of deposition is achieved (i.e.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…During the early phases of infection, macrophages and neutrophils provide essential innate defense against B. pseudomallei. However, macrophages also provide a potential intracellular niche for B. pseudomallei persistence and replication (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%